PENGARUH KEPUASAN TERHADAP LOYALITAS KONSUMEN PADA SWALAYAN SMART PASIR PENGARAIAN - afni, Nur (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
Goals that were examined in this study were: (1) To determine the effect of customer satisfaction SMART Self Sand Pengaraian (2) To determine the effect on customer loyalty SMART Sand Pengaraian Supermarkets (3) To determine the influence of satisfaction on customer loyalty in Supermarkets SMART Sand Pengaraian. Variables used in this research is customer satisfaction and customer loyalty. Methods of data collection using the questionnaire. The results showed that: There is the influence of customer satisfaction on customer loyalty with a coefficient of 0.62 and t = 4.306 with 0.000 significance. because of the significance> 0,05 so that Ho refused and Ha accepted. Ie the regression results obtained 22.969 + 0.621. The conclusions in this study are the effect of customer satisfaction on customer loyalty. Advice can be given in this study are: (1) The SMART Self Sand Pengaraian should conduct education and training for employees so as to improve its service to customers. Expected to subsequent researchers to examine other possible variables have an influence on customer loyalty.